Patient Experience and Satisfaction With Chiropractic Care: A Systematic Review - Dave Newell PhD; Michelle M Holmes PhD (Journal of Patient Experience)
Despite numerous studies that measure satisfaction in patients undergoing chiropractic care, these have not yet been systematically summarized. The aim of this study was to perform a systematic review of existing literature to identify factors that contribute to high levels of satisfaction in chiropractic care. A comprehensive search was conducted to identify quantitative, qualitative, or mixed-methods studies exploring patient experience with chiropractic care. Forty-three studies were included in the review. The findings showed that patient satisfaction was consistently high in comparison to other professions. The review identified key factors that contribute to patient experience, which were not limited to clinical outcomes, but also the clinical interaction and clinician attributes. The findings of this review provide a core insight into patient experience, identifying both positive and negative experiences not just within chiropractic care but in the wider healthcare sector. Further work should explore factors that impact patient satisfaction and how this understanding may further improve healthcare to enhance patient experience.